## Trending News

# Solve using the elimination method. Show your work. If the system has no solution or an infinite number of sol?

Solve using the elimination method. Show your work. If the system has no solution or an infinite number of solutions, state this.

-3x+4y=1, -6x+6y=-3

THIS IS WHAT I GOT

multiply yh first equation -3x+4y=1 by 2------- -6x+8y=1

then add 2nd equation -6x+6y=-3..... 12y=-2

y=-6

then -3x+4(-6)=1....-3x+-24=1

x=25...... am i right (25,-6) please help

### 6 Answers

- 9 years agoFavorite Answer
Rewriting the equations:

-3x+4y=1

-6x+6y=-3

Multiply (-3x+4y=1) by 2 to get: -6x+8y=2

Once again rewriting:

-6x+8y=2

-6x+6y=-3

Subtract the second equation from the first equation to eliminate x:

-6x+8y=2

-(-6x+6y=-3) (Here, distribute.)

2y=5, y=2.5

Plugging y in to equation 1 and rearranging:

-3x+4*2.5=1

-3x+10=1

-3x=-9

x=3

So, x=3 and y=2.5.

Your solution is (3,2.5)

- Anonymous9 years ago
Remember what you do to one side of the equation, you have do it on OTHER side also.

Your approach is right but you need to fix one thing. Look at your first step and there is the problem in your evaluation.

Second problem that I see is that you are adding -6 and -6, which doesn't cancel out but adds up to -12. Fix it by either multiplying your first equation by -2 or if you multiply by 2 then SUBTRACT instead of adding the equations.

Hope these guidelines help, I would give away the answer, but I think this would be more helpful.

- Anonymous9 years ago
You have at least one error. Correctly:

-6x+8y =2 (not 1)

-6x+6y = 3

2y= -1

y= -1/2

Substituting, -3x - 2 = 1

solving, x= -1

- 9 years ago
Your mistake was adding -6x to -6x which would be -12x

multiply the first equation by -2 and try again

- How do you think about the answers? You can sign in to vote the answer.
- ComoLv 79 years ago
6x - 8y = - 2

-6x + 6y = - 3_____ADD

-2y = - 5

y = 5/2

6x = - 2 + 20

6x = 18

x = 3

x = 3 , y = 5/2

- panic modeLv 79 years ago
divide second equation by -2 to get

3x-3y=3/2

then add it to first one

(-3x+4y) + (3x-3y)=(1)+(3/2)

y=5/2

etc.